Healthy Eating: Smart Snacking - Jennifer Hillan; Linda B. Bobroff (EDIS, 2010)
Revised! FCS8698, a 1-page handout by Jennifer Hillan and Linda B. Bobroff, provides smart snacking tips for elders in an easy-to-read format. Published by the UF Department of Family Youth and Community Sciences, March 2010.